Take control of your productivity - Porten, Jeff (Take control., 2018)
Increase Productivity and Reduce Stress!Being productive is never as simple as putting items on a calendar or to do list and checking them off. Most of us struggle with too much to do, too little time, and only a vague idea of how to plan each day so we can achieve the best results with the least stress. If that sounds like you (and especially if you've tried a bunch of productivity systems and found them lacking), Jeff Porten's expert guidance may be just what you need. As a professional technology consultant and an early adopter of both hardware and software, Jeff has tried nearly every productivity management system out there, and experimented with dozens of implementation styles. He brings his decades of experience to this book, helping you create a customized strategy that's ideal for your needs, and--crucially--avoid common mistakes. Whether you're a productivity junkie or someone who has struggled for years with a cobbled-together, informal task-management system, this book will help you get a much better grip on your personal and business time. In this book, you'll:Review the principles of successful planning--whether for immediate projects or for long-term and "someday" goals. Understand your natural working style and preferences, including comfortable habits that may not be productive but that you don't want to change, and create a more effective workflow that fits you. Discover the best ways to think about projects, tasks, events, due dates, flags, contexts, and more. Choose a task-management app that's appropriate for your needs, no matter what devices and operating systems you use, and that integrates with your calendar, reminders, notes, and the apps you use to actually do things. Develop a step-by-step process for tracking all your events and tasks and ensuring that everything happens in the right order. Transition from an old system to your new system without worrying that anything will fall through the cracks. Learn exactly how to keep track of all the things you need to remember throughout the day. Improve your time-estimation skills when planning how long future tasks and projects will take. Solve the problem of "10-minute tasks" that become all-day projects because they have a dozen things you discover you need to do first. Get better at managing other people (and their expectations of you). Review how well your productivity system has worked over time, using feedback loops and suggested best practices to continually improve your workflow. Fail successfully! If something goes wrong--from a derailing large project to a life-changing crisis--learn how to recover gracefully and improve your system the next time around. Know when and how to make changes to meet any new needs you have, and to ensure that what you do every Tuesday at 2 PM contributes to your overarching goals and most important roles in life. Although many of the examples in the book refer to Mac productivity tools, the advice is platform-neutral. The book contains tips applicable to any combination of operating systems, and a companion webpage provides additional details on apps running on Mac, Windows, iOS, Android, and the web